Alcohol induces α2‐6sialo mucin O‐glycans that kill U937 macrophages mediated by sialic acid‐binding immunoglobulin‐like lectin 7 (Siglec 7) - Pi‐Wan Cheng; Vishwanath‐Reddy Hothpet; Ganapati Bhat; Kristina Bailey; Lei Li; Derrick R. Samuelson (FEBS Open Bio)
Alcohol misuse increases infections and cancer fatalities, but mechanisms underlying its toxicity are ill‐defined. We show that alcohol treatment of human tracheobronchial epithelial cells leads to inactivation of giantin‐mediated Golgi targeting of glycosylation enzymes. Loss of core 2 N‐acetylglucosaminyltransferase 1, which uses only giantin for Golgi targeting, coupled with shifted targeting of other glycosylation enzymes to Golgi matrix protein 130‐Golgi reassembly stacking protein 65, the site normally used by core 1 enzyme, results in loss of sialyl Lewis x and increase of sialyl Lewis a and α2‐6sialo mucin O‐glycans. The α2‐6sialo mucin O‐glycans induced by alcohol cause death of U937 macrophages mediated by sialic acid‐binding immunoglobulin‐like lectin 7. These results provide a mechanistic insight into the cause of the toxic effects of alcohol and might contribute to the development of therapies to alleviate its toxicity.